DAMPAK PENYULUHAN TERHADAP MINAT PETANI DALAM BUDIDAYA TANAMAN CABE DI DESA HABAU HULU KEAMATAN BANUA LAWAS KABUPATEN TABALONG - Jauhar Jauhar; Sujono Sujono; Sunardi Sunardi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
This study aims to find out the interest of farmers in chili cultivation in Habau Hulu Village, Banua Lawas District, Tabalong Regency. This study used a quantitative descriptive method which was carried out from November 2022 to February 2023. The selection of Habau Hulu Village and farmer groups was carried out purposively, while the sampling of respondent farmers used proportional random sampling. The type of data used is primary data and secondary data is supporting data. Data collected through direct interviews with respondents using a questionnaire were then analyzed using a descriptive method which was analyzed using a Likert scale. The results of data analysis show that farmers' interest in chili cultivation in Habau Hulu Village is included in the high category with an average percentage of 78.63%, meaning that farmers who are included in farmer groups in Habau Hulu Village already understand, believe, and carry out cultivation. chili plants, but their application has not been maximized according to recommendations.